The factors that affect gripping comfort score, palmar contact pressure and fingers posture during gripping columnar objects - Kazuki HOKARI (The Japan Society of Mechanical Engineers, 2020)
In present study, human subject experiment including sensory evaluation was conducted to investigate gripping comfort during gripping spherical and columnar objects and to identify important factors that affect gripping comfort score. Contact pressure measurement using a pressure sensor sheet and fingers posture measurement using a motion capture system during each gripping task were then carried out to investigate the individual differences in gripping style and to reveal the differences in fingers posture according to the shapes of the test objects. As a result, significant differences in the gripping comfort score between male and female could not be found in all test objects. Additionally, the coefficients of determination of the relationship between the gripping comfort score and hand length and between the gripping comfort score and hand breadth were considered low in all test objects. Furthermore, a hierarchical cluster analysis of contact pressure distribution demonstrated that two gripping styles during gripping a cylinder existed in present study. Joint angles around x-axes of PIP joints of the middle finger and the ring fingers, around y-axis of CM joint of the thumb and around y-axes of MCP joints of the five fingers varied according to the gripping styles. Moreover, significant differences in 11 joint angles among test objects were confirmed based on the analysis result of fingers posture. This result indicates that fingers posture during gripping changes with the change of the shape of the test object. The results of present study provide information regarding important factors that should be considered or may not be considered during the evaluation and improvement of the gripping comfort of a manufactured product.